Perbandingan Kurikulum Merdeka PAUD Indonesia Dengan Kurikulum Standard Prasekolah Kebangsaan (KSPK) Malaysia - Galtar, Diana; Prastyo, Danang; Usman, Jamiludin; Umam, Khoirul (Institut Agama Islam Negeri Madura, 2025)
This article discusses the comparison between the Merdeka PAUD Curriculum in Indonesia and the National Preschool Standard Curriculum (KSPK) in Malaysia. This research uses descriptive qualitative methods with the aim of identifying similarities and differences between the two curricula in the context of early childhood development. Document analysis and literature studies show that the KSPK and Merdeka PAUD Curriculum have similarities in their focus on children's holistic development and the use of a fun learning approach. However, there are differences in content focus and learning approaches. KSPK places more emphasis on play-based learning, while the Merdeka PAUD Curriculum focuses on developing religious values and character as well as basic literacy and STEAM. This article provides implications for educational practitioners in Indonesia and Malaysia in understanding and implementing both curricula effectively, as well as providing recommendations for more optimal curriculum development in the future.